Neurocognitive Remediation Therapy for Depression. Issue 8 (August 2015) - Semkovska, Maria; Lambe, Sinead; Lonargáin, Diarmaid Ó; McLoughlin, Declan M.
<x xml:space="preserve">Abstract</x> Abstract Major depression is the most prevalent psychiatric disorder with high relapse rates. When mood can improve or fully recover, the neurocognitive difficulties associated with depression often persist, preventing complete functional recovery. They have also been shown to predict relapse. The efficacy of neurocognitive remediation therapy (NCRT) to rehabilitate cognition has been demonstrated in several clinical populations but randomized controlled trials (RCTs) have not been conducted in depression. The present study aimed to test the feasibility and to conduct a pilot protocol testing for an RCT of computerized NCRT for inpatients with major depressive episode. The feasibility assessment demonstrated excellent acceptance of randomization and very satisfactory recruitment and compliance rates. The RCT procedures' assessment was overall consistent with a successful pilot study with the condition of protocol modification in terms of resources. Preliminary outcome data suggested specific NCRT efficacy to improve targeted neurocognitive processes in depression.